Perbedaan Usia Menarche Siswa SMP Ditinjau dari Etnis Jawa, Tionghoa dan Arab di Surakarta - Rakhmawati, Isna Noor; Moelyo, Annang Giri; Karini, Suci Murti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background :Menarche is the first menstrual period in woman reproduction cycle. In many studies, race and ethnicity has been shown to contribute to the age of menarche. The objective of thisstudy is to identify the difference of menarcheâs agein junior high school girls among Javanese, Chinese and Arabian ethnic in Surakarta. Method :This wasa cross sectional study. Two hundred and thirty healthy Javanese, Chinese and Arabian students from 8th grade ofÂ 3 junior high schools in Surakarta were fulfilledthe restriction criteria. Age of menarche and ethnicity of the students were collected through a questionnaire. The difference of menarcheâs ageamong those three ethnics were analyzed by Kruskal Wallis in SPSS 17.0 for Windows. Result :Of 230 subjects, 151 (65.65%) students were Javanese, 42 (18.26%) students were Chinese and 37 (16.09%) students were Arabian. Two hundred and fourteen (93.04%) students had recently experienced menarche. The mean age of menarche was 11.9 (SD 0.85) years old and the youngest age of menarche was 9.9 years old. The mean age of menarche in Javanese was 12 years old, in Chinese was 11.8 years old and in Arabian was 11.9 years old. Kruskal Wallis test revealed no significant difference found in the age of menarche among Javanese, Chinese and Arabian (p = 0.567). Conclusion :There is no difference of menarcheâs age in junior high school girls among Javanese, Chinese and Arabian ethnic in Surakarta. Keyword :Ethnic,Menarcheâs Age Â